The Relationship between Service Quality and Customer Satisfaction on Electronic Banking Services: the Case of Ahantaman Rural Bank, Ghana - Ama Sesseh Krah; Oscar Agyemang Opoku; Amos Agyeman Oduro; Isaac Opoku- Dadzie; Owusu-Debrah Mark (HM Journals, 2022)
Many banks specifically rural banks, in the quest to improve their service quality for the benefit of their clients have joined the ride to adopt electronic banking. The study sought to examine the relationship between service quality and customer satisfaction in electronic banking services, with Ahantaman Rural Bank being the bank in focus. Using quantitative methodology, the study employed questionnaires to collect primary data for the analysis. The results showed that customers found ease of use, privacy and security, control, reliability, enjoyment, and speed of use as significant service quality dimensions expected of electronic banking services. This paper contributes to literature by offering a critical and comprehensive review of the relationship between service quality and customer satisfaction in electronic banking services and how important it is to continuously improve service quality of banks’ entire operations.